Dysregulated expression of hypoxia-inducible factors augments myofibroblasts differentiation in idiopathic pulmonary fibrosis - Arnoldo Aquino-Gálvez; Georgina González-Ávila; Laura Lorena Jiménez-Sánchez; Héctor Aquiles Maldonado-Martínez; José Cisneros; Fernanda Toscano-Marquez; Manuel Castillejos-López; Luz María Torres-Espíndola; Rafael Velázquez-Cruz; Víctor Hugo Olivera Rodríguez; Edgar Flores-Soto; Héctor Solís-Chagoyán; et al. (Respiratory Research, 2019)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is an age-related, progressive and lethal disease, whose pathogenesis is associated with fibroblasts/myofibroblasts foci that produce excessive extracellular matrix accumulation in lung parenchyma. Hypoxia has been described as a determinant factor in its development and progression. However, the role of distinct members of this pathway is not completely described. Methods By western blot, quantitative PCR, Immunohistochemistry and Immunocitochemistry were evaluated, the expression HIF alpha subunit isoforms 1, 2 & 3 as well, as their role in myofibroblast differentiation in lung tissue and fibroblast cell lines derived from IPF patients. Results Hypoxia signaling pathway was found very active in lungs and fibroblasts from IPF patients, as demonstrated by the abundance of alpha subunits 1 and 2, which further correlated with the increased expression of myofibroblast marker αSMA. In contrast, HIF-3α showed reduced expression associated with its promoter hypermethylation. Conclusions This study lends further support to the involvement of hypoxia in the pathogenesis of IPF, and poses HIF-3α expression as a potential negative regulator of these phenomena.